Bioinformatic Description of Immunotherapy Targets for Pediatric T-Cell Leukemia and the Impact of Normal Gene Sets Used for Comparison - Orentas, Rimas J.; Nordlund, Jessica; He, Jianbin; Sindiri, Sivasish; Mackall, Crystal; Fry, Terry J.; Khan, Javed (Frontiers in Oncology, 2014)
Pediatric lymphoid leukemia has the highest cure rate of all pediatric malignancies, yet due to its prevalence, still accounts for the majority of childhood cancer deaths and requires long-term highly toxic therapy. The ability to target B-cell ALL with immunoglobulin-like binders, whether anti-CD22 antibody or anti-CD19 CAR-Ts, has impacted treatment options for some patients. The development of new ways to target B cell antigens continues at rapid pace. T-cell ALL accounts for up to 20% of childhood leukemia but has yet to see a set of high value immunotherapeutic targets identified. To find new targets for T-ALL immunotherapy, we employed a bioinformatic comparison to broad normal tissue arrays, hematopoietic stem cells (HSC), and mature lymphocytes, then filtered the results for transcripts encoding plasma membrane proteins. T-ALL bears a core T cell signature and transcripts encoding TCR/CD3 components and canonical markers of T cell development predominate, especially when comparison was made to normal tissue or HSC. However, when comparison to mature lymphocytes was also undertaken, we identified two antigens that may drive, or be associated with leukemogenesis; TALLA-1 and hedgehog interacting protein, HHIP. In addition, TCR subfamilies, CD1, activation and adhesion markers, membrane organizing molecules, and receptors linked to metabolism and inflammation were also identified. Of these, only CD52, CD37, and CD98 are currently being targeted clinically. This work provides a set of targets to be considered for future development of immunotherapies for T-ALL.